Patients Who Attend the Emergency Department Following Medication Overdose: Self-reported Mental Health History and Intended Outcomes of Overdose - Buykx, P.; Ritter, A.; Loxley, Wendy; Dietze, P. (Springer, 2011)
Abstract Medication overdose is a common method of non-fatal self-harm. Previousstudies have established which mental health disorders are commonly associated with thebehaviour (affective, substance use, anxiety and personality disorders) and whichmedications are most frequently implicated (benzodiazepines, antidepressants, antipsychoticsand non-opioid analgesics). However, few studies have explored patient experiencesof medication overdose. We address this gap by examining patient stories of a recentmedication overdose event, including severity of depression, intended outcomes and patientexperiences of emergency medical care, in part to determine the unmet needs of this groupof patients. Semi-structured interviews were conducted with 31 patients attending an urbanEmergency Department (ED) in Melbourne, Australia, following a medication overdoseregarding their mental health history, state of mind at the time of the overdose,circumstances of the overdose, and experiences of emergency medical care. Participantswere heterogeneous regarding the severity of depressive symptomatology at the time ofoverdose. Participant ratings of how accidental or deliberate the overdose was and howstrongly they intended to die were also diverse. Stories relating to the overdose usuallycovered the themes of precipitating events, negative feeling states, and intended outcomes(ambivalent or contradictory). Few problems were identified in relation to the care receivedin relation to the current overdose. However, histories of extensive mental health problems